Fixed points in modular spaces with new type contractivity - Lal Shateri, Tayebe (International Journal of Applied Mathematical Research, 2014)
In this present paper, we prove a common _xed point theorem for self maps in modular spaces. Also one corollary, which shows that our main theorem is generalized version of the main theorem of [A. Razani, E. Nabizadeh, M.Beyg Mohamadi and S. Homaei Pour, Abs. Appl. Anal. 2007, Article ID 40575] is given.